Lexicon of Traditional Medicinal Plant in Deli Malay: An Ecolingustic Study - Zahra Rifasyah (TALENTA Publisher, 2025)
This study aims to analyze the segmental phonetic structure of four names of medicinal plants in Deli Malay, namely cinnamon (Cinnamomum verum), gambir (Uncaria gambir), lime (kapur sirih), and sirih (Piper betle). This study also connects linguistic data with the function of plants in the traditional medicinal culture of the Deli Malay community. Using qualitative descriptive methods and an articulatory phonetic approach, the results of the study indicate that each plant name has unique phonetic characteristics that reflect the phonotactic patterns of the language and the accompanying cultural functions. This study contributes to the preservation of local linguistic and ethnobotanical treasures.